Spatial Distribution of Heavy Metals in Al-Zarqa, Jordan - Reem Naser Dabaibeh (Indonesian Journal of Chemistry, 2021)
Al-Zarqa is experiencing challenges in industry conversion and extensive urbanization. The environmental quality of soil in the Al-Zarqa region was analyzed by Spatial analysis for the identification of sources and estimation of the concentration of heavy metals, which helped in the assessment of soil quality and heavy metal pollution. The reason for the elevation of heavy metal pollution is increased urbanization, industrialization, traffic, oil refinery emissions, and mixed anthropogenic sources in that region. The main objective of this research was to assess the ecological impact of heavy metals pollutants in the Al-Zarqa region. The concentrations of (Cd, Cr, Cu, Mn, Ni, Pb, Zn, and Fe) were estimated and compared with the existing literature. The distribution pattern of each metal was identified by spatial distribution analysis. Results revealed that metals concentration (Cd, Cr, and Ni) is higher, and the concentration of Pb, Zn, and Cu is less than the maximum allowed limits. Factor analysis identified the potential sources of heavy metals in the investigated area, and spatial distribution showed the geographical distribution of heavy metals over the study area. Consequently, it is better than showing only the individual point concentration without identifying their potential sources and their geographical variations.